Change of Function and Space of Puri in Bali: A Social History - A. A. Gde Djaja Bharuna S; P. R. Salain; G. A. M. Suartika; N. K. Acwin Dwijendra (Doctorate Program of Engineering Science, Faculty of Engineering, Udayana University, 2018)
Puri is one of the traditional Balinesearchitecture, which is a palace. The form is a complex ofbuildings that function as the center of government and theresidence of the king and his family. Like other palaces, puriin Bali has unique and distinctive features, making itinteresting to study.As time passes, Balinese traditionalarchitecture undergoes development and change, puri-puri inBali are also not free from that, in line with the developmentof Balinese socioculture. Changes in the puri in Bali basicallycaused by two main factors, namely external factors, as wellas internal factors. The research is aimed to intended toidentify factors causing changes in the puri, both in terms offunction and spatial. The study will be conducted with asocial-historical approach, an approach in the field ofarchitecture that has not been done. The proposition beginswith a description of the socio-cultural background of thecommunity and proceeds with a study of the physical changesthat occur. The results of the study are expected to be used toanticipate and control more worrying changes in the future